On Line Stator Resistance Tuning of DTC Control CSI Fed IM Drives - N. Panner selvam; M. Arul Prasanna; I. Gerald Christopher raj (International Journal of Power Electronics and Drive Systems (IJPEDS), 2012)
Current source inverter (CSI) fed drives are employed in high power applications. The conventional CSI drives suffer from drawbacks such as harmonic resonance, unstable operation at low speed ranges, and torque pulsation. CSI fed drives with Direct Torque Control (DTC) has drawn the attention of the motor drives designers because its implementation requires no position sensor. Crucial to the success of this scheme is the estimation of electromagnetic torque and stator flux linkages using the measured stator voltages and currents. The estimation is dependent only on one machine parameter, stator resistance. The variation of the stator resistance, deteriorates the performance of the drive by introducing errors in the estimated flux linkage’s magnitude and its position and hence in the electromagnetic torque. Resistance change also skews the torque linearity thus making the motor drive a less than ideal torque amplifier. Parameter compensation using stator current phasor error has been proposed in literature. To obtain the stator current phasor error, the stator current reference is required which is not usually available in direct torque control schemes. An analytical derivation of the stator current phasor reference is derived systematically from the reference electromagnetic torque and flux linkages. The error between the stator current phasor reference and its measured value is a measure of the stator resistance variation from its set value. For the first time, it is demonstrated in this paper that DTC motor drive system can become unstable when the set value of the stator resistance in the controller is higher than the stator resistance in the machine. Hence parameter adaptation is not only important for torque linearity but also for stability of the system is shown in this paper.DOI: http://dx.doi.org/10.11591/ijpeds.v2i2.332